IW Financial Expert Survey: First Quarter 2018 - Markus Demary (Institut der deutschen Wirtschaft (IW), 2018)
The IW Financial Expert Survey for the first quarter of 2018 revealed that the surveyed experts predict, on average, higher interest rates and stock market indices, a depreciation of the Euro vis-à-vis the US Dollar, and lower oil prices by the end of the first half of 2018. However, despite the expectation of higher interest rates, the short-term interest rate is predicted to remain in negative territory. Moreover, the experts expect the long-term interest rate to increase more compared to the short-term interest rate, which indicates a steeper yield curve. The 3-month Euribor is, on average, expected to reach -0.30 percent at the end of the second quarter of 2018, while the yield on German government bonds with 10-year maturity is expected to reach 0.60 percent by then. However, the experts do not expect the European Central Bank (ECB) to end net purchases of government bonds in the first half of 2018. The majority of the experts believe that the ECB will end net purchases at the end of 2018. No experts expect the ECB to increase its policy interest rates in 2018 or the first half of 2019. Instead, the majority of experts predict the first interest rate hike for the end of the second quarter of 2019. Some experts even predict a later date. Stock markets are, on average, expected to increase by 5.2 percent (Stoxx 50) and 4.8 percent (DAX 30) during the first half of 2018. During that same period, the experts predict the Euro will depreciate by 2.7 percent vis-à-vis the US Dollar, while oil prices are expected to fall 10.5 percent. The expectation of an increase in the long rate and a slight increase in the short rate, together with the expected delayed monetary tightening of the ECB, hint at a financial market outlook characterised by a cautious approach to monetary normalisation. In this cautious approach, the ECB lets the market determine the first increases in long-term interest rates before it stops in-tervening at the long end of the yield curve, while keeping the short end of the yield curve lower. This approach will prevent an inverted yield curve that would endanger financial stability. The experts' prediction that the ECB will first stop net purchases of government bonds and then lift its key policy interest rates would be consistent with the outlook of a cautious approach to mon-etary normalisation by the ECB. The evaluation of the forecasting performance of the latest forecasts indicates that Com-merzbank and Postbank performed best in predicting trends, while the experts from DZ Bank produced the most precise point forecasts. In the long-term evaluation of the period running from Dec 29 2014 to Dec 29 2017, the DZ Bank experts performed best in predicting trends, while the National Bank experts produced the most precise point forecasts.
Keywords: G12; G17; 330